â€œPENGARUH PEMBERIAN MIKORIZA ARBUSKULA DAN PUPUK ORGANIK TERHADAP PERTUMBUHAN BIBIT JATI PUTIH (Gmelina arborea Roxb.)â€ - Santoso, Anugrah Condro; Harwati, Tri -; -, Siswadi - (Innofarm:Jurnal Inovasi Pertanian, 2013)
Research on "The Effect of giving arbuscular mycorrhizal and Organic Fertilizer Against growth of white teak seedlings (Gmelina arborea Roxb.) has been started on April 2013 until July2013 at green house of agriculture faculty of Slamet Riyadi University which is located in Village Kadipiro,Subdistrict Banjarsari, Town Surakarta, Province Central Java. The research design was factorial Completely Randomized Design (CRD) consisting of 2 factor and 3 replication. Data were analyzed by Analysis of Variance (Anova), continued by Honestly Significant Diferent Test (HSDT) on 5 % significant level. The results show: Mycorrhizal best dose is 10 g / polybag because it can produce the highest seedlings height is 157.89 cm, weight of the fresh seedlings is 333.42 g toughest, heaviest and dry weightof seedlingsis 86.37 g,. Best organic fertilizer is compost because it can produce the highest seedlings height 13 cm, diameter of the largest trunk is 12.18 mm, the highest number of leaves is 30.33 leaves, fresh weight is 306.49 g toughest seedlings, and dry weight of seedlingsof the heaviest is 79,86 g., and Best interactions happen on a combination of compost with mycorrhizal dosage 10 g/polybag because it produces the smallest root-shoot ratio is 2.116, a combination of compost with mycorrhizal dosage of 15 g / polybag because it produces the smallest root-shoot ratio is 2.237, and the combination of mycorrhizal dose 10 g / polybag with cow dung manure because it produces the smallest root-shoot ratio is 2.175. Key words : arbuscular mycorrhizal, Organic Fertilizer, white teak